Evaluating sedimentation problems in activated sludge treatment plants operating at complete sludge retention time. (1st February 2015) - Amanatidou, Elisavet; Samiotis, Georgios; Trikoilidou, Eleni; Pekridis, George; Taousanidis, Nikolaos
Abstract: Zero net sludge growth can be achieved by complete retention of solids in activated sludge wastewater treatment, especially in high strength and biodegradable wastewaters. When increasing the solids retention time, MLSS and MLVSS concentrations reach a plateau phase and observed growth yields values tend to zero ( Y obs ≈ 0). In this work, in order to evaluate sedimentation problems arised due to high MLSS concentrations and complete sludge retention operational conditions, two identical innovative slaughterhouse wastewater treatment plants were studied. Measurements of wastewaters' quality characteristics, treatment plant's operational conditions, sludge microscopic analysis and state point analysis were conducted. Results have shown that low COD/Nitrogen ratios increase sludge bulking and flotation phenomena due to accidental denitrification in clarifiers. High return activated sludge rate is essential in complete retention systems as it reduces sludge condensation and hydraulic retention time in the clarifiers. Under certain operational conditions sludge loading rates can greatly exceed literature limit values. The presented methodology is a useful tool for estimation of sedimentation problems encountered in activated sludge wastewater treatment plants with complete retention time. Graphical abstract: State point analysis in complete mix extended aeration activated sludge system with pre-anoxic denitrification, at critical point of 15 kg MLSS m −3 and return activated sludge rate of 600% with complete solids retention time is given. The intersection of overflow and underflow line is the state point. State point's vertical projection on X axis shows the MLSS concentration in the aeration tank. The underflow line is well below the lower limb of gravity flux curve insuring good effluent quality. Highlights: Zero net biomass growth can be achieved by complete sludge retention. Low C/N ratios increase sludge flotation in clarifier. SLR can exceed literature values, when limited denitrification occurs in clarifier. Stirred and unstirred velocity tests indicate gas production in clarifier. State point analysis estimates and verifies sedimentation process critical points.